Inventario de atractivos turísticos naturales y culturales para promover el turismo en el cantón Quevedo, año 2020 - Lopez Chichande, Ana Alexandra (2021)
The Quevedo Canton is located in the Province of Los Rios, it is an economic city that is mainly dedicated to commerce, its population, according to the 2010 Census is located by 150,827 inhabitants, its blessed geographical situation places it in the center of unification of the roads between the coast and the central highlands, this benefits and strengthens its commercial activities, however, in recent years the Quevedo Canton has sought to generate an approach related to tourist activities, the emblem of "Ciudad del Rio" is a form social that compromises the tourist and cultural values of the city at a promotional level, seeking independence from its own attractions and promoting other additional or parallel activities to trade, agriculture or livestock. This information, as a result of the investigation, reveals a sequence of events that converge in a lack of tourist and cultural promotion focused on community development as a sustainable economic engine, however, on par with this reality, the authorities of the Municipal GAD of the The city of Quevedo establishes activation promotions for new tourist spaces in the urban area, promoting investment and development of the aforementioned spaces and at the same time underutilizing the other tourist and cultural spaces that the city has. The promotion of tourism in Ecuador has been promoted in recent years as a window of opportunity towards a better development of the economy in the country, the Quevedo canton seeks to generate a cultural and tourist image framed in the socioeconomic development that strengthens the local economy in a sustainable and sustained way over time.